Ultra-fast electro-reduction and activation of graphene for high energy density wearable supercapacitor asymmetrically designed with MXene - Karim, Golam Masud; Dutta, Pronoy; Majumdar, Abhisek; Patra, Amalika; Deb, Sujit Kumar; Das, Snehasish; Dambhare, Neha V.; Rath, Arup K.; Maiti, Uday Narayan (Carbon, 2023)
Controlled perforation of graphene is vital to surpass the performance of supercapacitors that rely on their pristine form. However, their practical utilization has been halted by energy-inefficient and lengthy processing. Here, we are reporting a pulse Joule heating strategy for on-site reduction and activation to realize a multimodal porous framework made of perforated graphene using millisecond current pulses. The multimodal porosity and surface functionalities of graphene were regulated at an ultrafast rate by passing a transient current. Asdeveloped ready-to-use electrode composed of nano-to-macro multimodal porosity displays high areal capacitance of 380.2 mF cm-2 in symmetric two-electrode configuration, which is nearly 1.6 times higher than the nonelectro activated counterpart. Furthermore, a high-performance wearable asymmetric supercapacitor with an areal energy density of 107.8 mu Wh cm-2 was realized using this multimodal porous graphene in combination with suitable negative electrodes made of MXene. High energy density, together with stable and repeatable performance of the wearable device for 10000 cycles of charge-discharge and 5000 cycles of bending, signifies the importance of the as-developed device for practical wearable applications. Direct, simple processing of electrodes and orders of magnitude lower cost-and-processing-time can make the process appealing for practical wearable and other energy storage applications.
Keywords: asymmetric supercapacitor; Graphene activation; Joule heating; Solid-state supercapacitor; Wearable device